2000
DOI: 10.1007/s002100000310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacology of P2Y-receptors

Abstract: Membrane-bound P2-receptors mediate the actions of extracellular nucleotides in cell-to-cell signalling. P2X-receptors are ligand-gated ion channels, whereas P2Y-receptors belong to the superfamily of G-protein-coupled receptors. So far, the P2Y family is composed of eight cloned and functionally defined subtypes. Five of them (P2Y1, P2Y2, P2Y4, P2Y6 and P2Y11) are present in human tissues. The P2Y3-, p2y8- and tp2y-receptors may be species orthologues. The principal physiological agonists of the cloned human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
445
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(468 citation statements)
references
References 107 publications
(134 reference statements)
21
445
1
1
Order By: Relevance
“…We did not detect any phosphorylation at Ser239 after UDP stimulation (data not shown), and phosphorylation at Thr278 could not be assessed because of lack of commercially available antibodies. There was only one report indicating that the P2Y 6 receptor couples with PLA activity [28], but it is known as a canonical pathway that P2Y 6 receptor activation leads to PKC activation [17]. Our results indicate that phosphorylation at Ser157 of VASP is mediated by PKC.…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Pkcsupporting
confidence: 48%
See 1 more Smart Citation
“…We did not detect any phosphorylation at Ser239 after UDP stimulation (data not shown), and phosphorylation at Thr278 could not be assessed because of lack of commercially available antibodies. There was only one report indicating that the P2Y 6 receptor couples with PLA activity [28], but it is known as a canonical pathway that P2Y 6 receptor activation leads to PKC activation [17]. Our results indicate that phosphorylation at Ser157 of VASP is mediated by PKC.…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Pkcsupporting
confidence: 48%
“…Stimulation of the P2Y 6 receptor also leads to PKC activation by PLC signaling [17]. We investigated the effects of three PKC inhibitors, Bisindolylmaleimide I (Bis), Gö6976 (Gö76) and Gö6983 (Gö83), on both UDP-stimulated reactions, each with different selectivity for the PKC subtypes.…”
Section: Udp Induced the Phosphorylation And Translocation Of Vaspmentioning
confidence: 99%
“…Moreover, in presence of PPADS, a non-selective P2 receptor antagonist, intracellular [Ca 2+ ] i mobilization was completely blocked. Of note, it is reported that the P2Y1 subtype has a widespread expression and is involved in blood platelet aggregation, vasodilatation and neuromodulation [23,28]. RT-PCR evaluation of P2Y receptors revealed P2Y1, P2Y2, P2Y4, and P2Y6 receptor expression during the time course of ES cell differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…The P2Y1 receptor is a major subtype expressed generally in all cell types, and it mainly involves in regulating cell proliferation and differentiation. Interestingly, the principal physiological agonist for P2Y1 is ADP rather than ATP [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the derivatives were found to inhibit the activity of extracellular nucleotides through G protein-coupled P2Y receptors and subsequent biochemical steps. Eight mammalian subtypes of [18][19][20][21] such receptors (P2Y 1,2,4,6,[11][12][13][14] are currently sequence-defined. The P2Y receptors are present in the cardiovascular, immune, and nervous systems, as well as in other systems.…”
Section: Introductionmentioning
confidence: 99%